Pengaruh Pemberian Umpan dan Daun Salam (Syzygium polyanthum) terhadap Perilaku Kecoa Amerika (Periplaneta americana) - Dwi, Yohanna Aresta; Ramli, Murni (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2022)
This study aims to determine the behavior caused by the American cockroach (Periplaneta americana) due to bait and bay leaf (Syzygium polyanthum). The research method used is a quantitative (experimental) method using a completely randomized design (CRD) consisting of 3 treatments with 3 times variations. The results showed the behavior of cockroaches that approached the bait and bay leaf. In the first treatment (P1) as a control in the form of 5 grams of bait showed clear results that the behavior of the cockroach approached the bait. In the second treatment (P2) in the form of 5 grams of bait and 3 grams of bay leaves showed a repellent power of 20%. While in the three treatments (P3) in the form of 5 grams of bait and 10 grams of bay leaves, the repellant power was 26.67%. Based on this, the bay leaf is still less effective to be used as a natural cockroach repellent or repellent. So it can be said that the provision of bait and bay leaf (Syzygium polyanthum) to the American cockroach (Periplaneta americana) resulted in  similar behavior.